Associations between societal disapproval and changes in symptoms of PTSD and appetitive aggression following treatment among high-risk South African males. Issue 1 (1st January 2017) - Sommer, Jessica; Hinsberger, Martina; Holtzhausen, Leon; Kaminer, Debra; Seedat, Soraya; Elbert, Thomas; Augsburger, Mareike; Maercker, Andreas; Weierstall, Roland
ABSTRACT: Background : In violent communities, social rejection as a person with victim–offender attributes is associated with more intense symptoms of posttraumatic stress disorder (PTSD) and a higher propensity towards violence, i.e. appetitive aggression. Successful community reintegration encompassing adequate social acknowledgment of individuals with both a history of violence exposure and perpetration may be necessary to enhance the treatment effects of interventions addressing PTSD and aggression. Objective : In this study, the effects of treatment and post-treatment traumatic events, violent offenses, and social acknowledgment (with sub-dimensions of general disapproval, family disapproval, and recognition as a person with both a history of violence exposure and commission) on changes in PTSD symptom severity and appetitive aggression from baseline to 8-month follow-up were investigated. Method : Data were collected from 54 males recruited through a Cape Town offender reintegration programme for an intervention study targeting trauma and aggression ( n =  28 treatment; n =  26 wait-list). Changes in PTSD symptom severity after treatment were assessed with the PTSD Symptom Scale-Interview, changes in appetitive aggression with the Appetitive Aggression Scale (AAS), post-treatment traumatic events with an adapted version of the Child's Exposure to Violence Checklist, offenses with an adapted checklist from the AAS, and social acknowledgment with an adapted form of the Social Acknowledgment Questionnaire. Results : Path analyses revealed negative relationships between ongoing societal disapproval and changes in PTSD symptom severity and appetitive aggression at 8-months, controlling for age. All other variables were non-significant, except for treatment, which was associated with PTSD symptom reduction. Conclusions : As a complementary strategy to effective psychotherapeutic treatment, increased social acknowledgment may contribute significantly to the alleviation of PTSD symptoms and appetitive aggression. Psychological interventions should, therefore, not neglect the impact of societal factors on treatment effects.